PENGARUH PERILAKU BELAJAR DAN KECERDASAN EMOSIONAL TERHADAP STRES KULIAH - Setiawan, Joko (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
Research was conducted with the purpose of analyzing the behavior is to learn the influence of intellect and emotional stress for students studying accounting. Behavior learning consist of habit of following the lessons, practice reading books, visiting libraries, and the practice exam. Results of this research show that accounting students learning behavior provide a positive influence on the college stress, while the emotional quotient of accounting students have a significantly negative influence on the college stress. In this case the variables provide emotional intelligences more dominant influence on the college stress compared to behavioral variables studied